Healthy Diet Reflection in Tamil Proverbs : An Inquisitive Semantic Research - Mary Fatimah, Subet; Tangaprabu, Murthy; Muhammad Zaid, Daud (Scientific and Publishing Institute (Lembaga Publikasi Ilmiah dan Penerbitan), 2019)
Healthy eating practices, especially those based on food pyramid, should be vividly followed in our daily diet. The food pyramid guide contains four main groups of food which are arranged accordingly to the quantity of nutrition recommended by the health expertise of the balanced, healthy and correct nutritional features. One of the most vital part of the food pyramid is green vegetables and fruits. They are a the second level of the aforementioned food group that is rich in vitamins, minerals and fibre. Implicitly, this healthy eating image was also transmitted into the creation of proverbs for example in Tamil proverbs. Healthy food images have been detected in the Tamil data collection collected through deep interviews with four Indian informants. A total of five Tamil proverbs have been screened using sampling mode, which is aimed to have the images of green vegetables and fruits such as ‚eggplant‛, ‚cassava‛, ‚water pumpkin‛ and more. They were detected in a total of 25 Tamil proverbs obtained from the informants. Further to that, this study will examine the implicit meaning of these proverbs using an incredibly inquisitive approach by Nor Hashimah Jalaluddin (2014) by associating the data, theory, cognitive and intellect of the speakers. With such information, researchers are able to look at the language, society and thoughts of the speaker..